Relevant codes and regulations: Effects on the design of industrial construction - Abdallah, Ahmed (Technological and Economic Development of Economy, 2007)
This paper presents the possible effects and restrictions that may arise in the field of industrial construction due to compliance with relevant construction codes and regulations, as well as the ways they can be favourably handled in the design of industrial buildings. Designs should be based primarily on human design factors, while considering the human as the centre of the work environment. Design parameters should be described as a function of both the physical and psychosocial attributes of a person as well as the technical and economical aspects in the design of industrial construction. This paper is an examination of the connection that exists between design law (codes and regulations) and industrial construction. The relevant construction laws and regulations are described, including standards and codes of practice that designing and supervising engineers are obliged to observe. Possible solutions and consequences of development in the production, constructional, and ergonomic field of design are also discussed.Specialių įstatymų ir reglamentų įtaka pramoninių pastatų projektavimuiSantrauka. Šiame straipsnyje aprašomi galimi padariniai ir suvaržymai, kurie gali atsirasti pramoninių pastatų statyboje laikantis atitinkamų statybos įstatymų ir reglamentų, taip pat būdai, kuriuos galima būti tinkamai pritaikyti pramoninei statybai projektuoti. Projektuose visų pirma turi būti atsižvelgiama į žmogiškuosius veiksnius, žmogų laikant darbo aplinkos branduoliu. Projekto rodikliai turi būti apibūdinami funkcija, priklausančia nuo fizinių ir psichosocialinių asmens savybių, taip pat techninių ir ekonominių aspektų, darančių įtaką pramoninių pastatų projektiniams sprendimams. Šiame straipsnyje tiriamos sąsajos tarp projektavimo normų ir pramoninės statybos pavyzdžių. Aprašyti su statyba susiję teisės aktai ir reglamentai, taip pat tie, kurių turi laikytis projektuotojai ir statytojai. Straipsnyje taip pat svarstomi projektavimo patobulinimai gamybiniu, konstrukciniu, ergonominiu aspektais.Reikšminiai žodžiai: statybos įstatymai ir reglamentai, ekonominis pramoninių pastatų projektavimas.First Published Online: 21 Oct 2010